Uric Acid Induces a Proatherothrombotic Phenotype in Human Endothelial Cells by Imbalancing the Tissue Factor/Tissue Factor Pathway Inhibitor Pathway - Cimmino, Giovanni; Conte, Stefano; Marra, Laura; Morello, Andrea; Morello, Mariarosaria; De Rosa, Gennaro; Pepe, Martino; Sugraliyev, Akhmetzhan; Golino, Paolo; Cirillo, Plinio (Thrombosis and Haemostasis, 2022)
Background Several evidence show that elevated plasma levels of uric acid (UA) are associated with the increased risk of developing atherothrombotic cardiovascular events. Hyperuricemia is a risk factor for endothelial dysfunction (ED). ED is involved in the pathophysiology of atherothrombosis since dysfunctional cells lose their physiological, antithrombotic properties. We have investigated whether UA might promote ED by modulating the tissue factor (TF)/TF pathway inhibitor (TFPI) balance by finally changing the antithrombotic characteristics of endothelial cells.Methods Human umbilical vein endothelial cells were incubated with increasing doses of UA (up to 9 mg/dL). TF gene and protein expressions were evaluated by real-time polymerase chain reaction (PCR) and Western blot. Surface expression and procoagulant activity were assessed by FACS (fluorescence activated cell sorting) analysis and coagulation assay. The mRNA and protein levels of TFPI were measured by real-time PCR and Western blot. The roles of inflammasome and nuclear factor-κB (NF-κB) as possible mechanism(s) of action of the UA on TF/TFPI balance were also investigated.Results UA significantly increased TF gene and protein levels, surface expression, and procoagulant activity. In parallel, TFPI levels were significantly reduced. The NF-κB pathways appeared to be involved in modulating these phenomena. Additionally, inflammasome might also play a role.Conclusion The present in vitro study shows that one of the mechanisms by which high levels of UA contribute to ED might be the imbalance between TF/TFPI levels in endothelial cells, shifting them to a nonphysiological, prothrombotic phenotype. These UA effects might hypothetically explain, at least in part, the relationship observed between elevated plasma levels of UA and cardiovascular events.
Keywords: uric acid; inflammation; tissue factor; TFPI